2006
DOI: 10.2527/jas.2005-761
|View full text |Cite
|
Sign up to set email alerts
|

Chlortetracycline supplementation of yearling dairy heifers1,2

Abstract: Chlortetracycline is an antibiotic that is used to increase weight gain, efficiency of gain, carcass grade, and conception rates. The objective of this experiment was to evaluate the effects of supplementation of 350 mg/d of chlortetracycline on ADG, G:F, BCS, thyroxine, and systemic glucose concentrations in yearling dairy heifers. Forty 12-mo-old Holstein heifers (initial BW = 363 +/- 21 kg) were housed in a free-stall barn with ad libitum access to feed and water for 104 d. A transition period was begun 14 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 11 publications
1
2
0
Order By: Relevance
“…In this study, thyroxine concentrations were not different among treatments, which may partially explain the lack of skeletal growth in reference to hip and withers height improvement associated with CTC. Similar to the results of this study, Reid et al (2006) did not observe an increase in growth in CTC-supplemented dairy heifers or a difference in mean sera thyroxine concentrations. In our study, thyroxine may not have been affected either because of the CTC feeding regimen used or a potential breed difference in this response between beef and dairy heifers.…”
Section: Discussionsupporting
confidence: 90%
“…In this study, thyroxine concentrations were not different among treatments, which may partially explain the lack of skeletal growth in reference to hip and withers height improvement associated with CTC. Similar to the results of this study, Reid et al (2006) did not observe an increase in growth in CTC-supplemented dairy heifers or a difference in mean sera thyroxine concentrations. In our study, thyroxine may not have been affected either because of the CTC feeding regimen used or a potential breed difference in this response between beef and dairy heifers.…”
Section: Discussionsupporting
confidence: 90%
“…In eight studies in fattening cattle, only two studies including a dietary chlortetracycline supplementation at 35 mg chlortetracycline/kg DM (Beacom et al, 1988;Baldwin et al, 2000) showed growth-promoting effects. On the contrary, in other four studies, a dietary chlortetracycline supplementation at the same range of concentration in feed did not affect animal performance: 11 and 36-39 mg chlortetracycline/kg DM (Stanford et al, 2015); 38 mg chlortetracycline/kg DM (Kitts et al, 2007); 40 mg chlortetracycline/kg DM (Kitts et al, 2006;Reid et al, 2014). Equally, no effects on growth performance were observed when chlortetracycline was supplemented at 9 mg chlortetracycline/kg DM (Brown et al, 1975) or 589 mg chlortetracycline/kg DM (Cabral et al, 2013).…”
Section: Ruminantsmentioning
confidence: 88%
“…In the study of Reid et al. ( 2014 ) a total of 40 Holstein heifers (BW 363 kg, 12‐month‐old) were allocated to one of two dietary treatments. The basal diet was either not supplemented (control) or supplemented with chlortetracycline (unspecified chemical form; Aureomycin 90, Alpharma Inc., Fort Lee, NJ, USA) at a concentration of 350 mg/head/day (corresponding to ca.…”
Section: Assessmentmentioning
confidence: 99%